A Survey on UAV-Assisted Wireless Communications: Challenges, Technologies, and Application - Owaid, Sara A.; Miry, Abbas H.; Salman, Tariq M. (International Conference on Electrical and Electronics Engineering, 2024)
Unmanned Aerial Vehicles (UAVs) have attracted significant attention in recent years due to their potential for several applications, including wireless communication. Unmanned Aerial Vehicles (UAVs) possess the capacity to function as aerial base stations, relays, or data collection equipment, hence enabling efficient and flexible wireless communication in various scenarios. This survey article provides a thorough analysis of the current state-of-the-art in wireless communication facilitated by unmanned aerial vehicles (UAVs). This research investigates the intricacies, progressions, and pragmatic applications of incorporating unmanned aerial vehicles (UAVs) to enhance wireless communication infrastructures. The survey covers various aspects, including UAV deployment strategies, communication architectures, resource allocation, networking protocols, and regulatory considerations. Furthermore, it presents a detailed analysis of the key enabling technologies such as UAV mobility management, energy efficiency, interference mitigation, and communication range extension. Additionally, the paper discusses the emerging applications of UAV-assisted wireless communication in areas such as disaster management, rural connectivity, surveillance, and the Internet of Things (IoT). Finally, open research challenges and future directions are identified to guide researchers and practitioners in this rapidly evolving field.